Five-year outcomes from a prospective trial of image-guided accelerated hypofractionated proton therapy for prostate cancer. (3rd July 2017) - Henderson, Randal H.; Bryant, Curtis; Hoppe, Bradford S.; Nichols, R. Charles; Mendenhall, William M.; Flampouri, Stella; Su, Zhong; Li, Zuofeng; Morris, Christopher G.; Mendenhall, Nancy P.
Abstract: Purpose: To report 5-year outcomes of a prospective trial of image-guided accelerated hypofractionated proton therapy (AHPT) for prostate cancer. Patients and methods: 215 prostate cancer patients accrued to a prospective institutional review board-approved trial of 70Gy(RBE) in 28 fractions for low-risk disease ( n = 120) and 72.5Gy(RBE) in 29 fractions for intermediate-risk disease ( n = 95). This trial excluded patients with prostate volumes of ≥60 cm 3 or International Prostate Symptom Scores (IPSS) of ≥15, patients on anticoagulants or alpha-blockers, and patients in whom dose-constraint goals for organs at risk (OAR) could not be met. Toxicities were graded prospectively according to Common Terminology Criteria for Adverse Events (CTCAE), version 3.0. This trial can be found on ClinicalTrials.gov (NCT00693238). Results: Median follow-up was 5.2 years. Five-year rates of freedom from biochemical and clinical disease progression were 95.9%, 98.3%, and 92.7% in the overall group and the low- and intermediate-risk subsets, respectively. Actuarial 5-year rates of late radiation-related CTCAE v3.0 grade 3 or higher gastrointestinal and urologic toxicities were 0.5% and 1.7%, respectively. Median IPSS before treatment and at 4+ years after treatment were 6 and 5 for low-risk patients and 4 and 6 for intermediate-risk patients. Conclusions: Image-guided AHPT 5-year outcomes show high efficacy and minimal physician-assessed toxicity in selected patients. These results are comparable to the 5-year results of our prospective trials of standard fractionated proton therapy for patients with low-risk and intermediate-risk prostate cancer. Longer follow-up and a larger cohort are necessary to confirm these findings.